2018
DOI: 10.3389/fncel.2018.00203
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Rods, Cones, and Melanopsin in Photoresponses of M4 Intrinsically Photosensitive Retinal Ganglion Cells (ipRGCs) and Optokinetic Visual Behavior

Abstract: Intrinsically photosensitive retinal ganglion cells (ipRGCs) mediate not only image-forming vision like other ganglion cells, but also non-image-forming physiological responses to light such as pupil constriction and circadian photoentrainment. All ipRGCs respond to light through their endogenous photopigment melanopsin as well as rod/cone-driven synaptic inputs. A major knowledge gap is how melanopsin, rods, and cones differentially drive ipRGC photoresponses and image-forming vision. We whole-cell-recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 70 publications
5
35
0
Order By: Relevance
“…Although we use 'percent persistent' to describe differences between the cone-and melanopsin-driven pupil responses, we find that all stimuli evoke some degree of persistent response. This observation is consistent with prior work, both in previous PIPR studies that show that the red stimulus evokes persistent pupil constriction, as well as neurophysiologic studies that show ipRGCs generate persistent firing from nonmelanopsin inputs 38 . We examined as well the τexponential timing parameter of our model fits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although we use 'percent persistent' to describe differences between the cone-and melanopsin-driven pupil responses, we find that all stimuli evoke some degree of persistent response. This observation is consistent with prior work, both in previous PIPR studies that show that the red stimulus evokes persistent pupil constriction, as well as neurophysiologic studies that show ipRGCs generate persistent firing from nonmelanopsin inputs 38 . We examined as well the τexponential timing parameter of our model fits.…”
Section: Discussionsupporting
confidence: 92%
“…Blue light also drives S-cones, which, like melanopsin, produce delayed and sustained pupil responses 35 . While there is convincing evidence that sustained pupil constriction can be produced by melanopsin alone 11 , cones may also contribute (perhaps via the ipRGCs) to a sustained response [36][37][38] . Therefore, while the PIPR response reflects (perhaps overwhelmingly) the contribution of melanopsin signals, it cannot be concluded that differences between clinical populations in PIPR responses are attributable solely to the melanopsin system.…”
Section: Introductionmentioning
confidence: 99%
“…Though color opponency has been reported to be a defining feature of M5 ipRGCs, we found that all M4 ipRGCs consistently exhibit color opponency when recording in similar, light‐adapted conditions. M4 ipRGCs (ON‐alpha RGCs) receive strong rod input (Grimes, Schwartz, & Rieke, ; Schroeder et al, ; Wang, Weick, & Demb, ), which provides excitatory drive in response to a light stimulus delivered from darkness. This pathway is likely significantly bleached by the full‐field light that we used to identify M4 ipRGCs in our “light‐adapted” experiments (Figures and ), which would allow for the inhibitory response described previously from wide‐field amacrine cells to dominate (Farrow et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with prior work, both in previous PIPR studies that show that the red stimulus evokes persistent pupil constriction, as well as neurophysiologic studies that show ipRGCs generate persistent firing from nonmelanopsin inputs. 37 We examined as well the τ exponential timing parameter of our model fits. The melanopsin-directed and PIPR blue stimuli produced responses with greater τ exponential values as compared with their cone-directed and PIPR red counterparts.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Although there is convincing evidence that sustained pupil constriction can be produced by melanopsin alone, 11 cones may also contribute (perhaps via the ipRGCs) to a sustained response. 36 , 37 Therefore, although the PIPR response reflects (perhaps overwhelmingly) the contribution of melanopsin signals, it cannot be concluded that differences between clinical populations in PIPR responses are attributable solely to the melanopsin system.…”
mentioning
confidence: 99%